Photochemical synthesis of gold nanorods catalyzed by titanium dioxide - Jin, Yan (2010)
Gold nanorods can be synthesized by a photochemical approach. In this report, a mixture solution of HAuCl4, TiO2, HCl and ethanol was irradiated by a halogen light source. Ethanol reduced Au3+ to Au0 upon light irradiation. The TiO2 acted as both catalyst and stabilizer. TiO2 has a large band gap, which enables it to absorb short wavelength light. TiO2 produces free electrons and holes, thus promotes redox reaction of HAuCl4 and ethanol. TiO2 is positive in charge, thus it can absorb onto the gold nanoparticles, which are negative in charge, to avoid the aggregation. The gold nanorods were characterized by using UV-Vis absorption spectroscopy, X-ray diffraction and scanning electron microscopy. It is found that the amount of the HAuCl4 and the TiO2 to ethanol volume ratio affected the yield and length of the gold nanorods. The best gold nanorods were synthesized by using 0.1mmol HAuCl4 and with ethanol/TiO2 (1:3 in volume), and the length is around 2.5µm.